PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENANGANI KENAKALAN SISWA KELAS VIII DI SMP MUHAMMADIYAH SUKOHARJO - Fatayatur; Nur Hidayah; M. Yunan Hidayat (STAI Pelabuhan Ratu, 2023)
This study explores the role of Islamic Education (PAI) instructors in managing the behavior of eighth-grade students at SMP Muhammadiyah Sukoharjo. The aim of this research is to uncover the primary contributions of PAI teachers in addressing students' negative behavior and providing positive guidance through moral and religious approaches. Utilizing a qualitative research method, data were gathered through interviews, field observations, and document analysis. The results of the analysis indicate that PAI instructors play a significant role in guiding students towards good and positive behavior by applying Islamic values, moral principles, and character development. The study emphasizes the importance of Islamic education as a foundation for moral behavior and character formation, involving the roles of all teachers, the school environment, and also the parents of students at SMP Muhammadiyah Sukoharjo. These findings offer valuable insights into the role of PAI instructors in shaping the attitudes and behavior of students in an Islamic educational environment.